PERANCANGAN SISTEM MONITORING DAN PENGENDALIAN LAMPU MENGGUNAKAN SENSOR GERAK DAN SENSOR CAHAYA DILENGKAPI INTERNET OF THINGS (IOT) - COMPUTING INFORMATIKA; Nurul Imamah (Program Studi Teknik Informatika FTI UNIBBA, 2021)
In general the control of electronic devices such as lighting each uses a manual system. With this system we still have to press the switch if we want to turn the lights on and off. For this reason, the authors in this study propose to design a lamp control system so that the lamp can be monitored and controlled remotely and can find out the state of the lamp in real time, so that the lighting can be adjusted as needed. The purpose of this research is to design a monitoring and control system for lamps so that electricity consumption in lamp lighting is more effective and efficient by using motion sensors and light sensors equipped with the Internet of Things (IoT). The methodology used is Research and Development (R&D). The development model used in this study is the ADDIE model with the stages of Analysis, Design, Development, Implementation and Evaluation. The result of this research is the application can function properly according to the analysis and design made. Then the application can monitor the control of the lights using motion sensors and light sensors, monitor the scheduling of the lights, find out the duration of the lights and control the lights directly with the internet through the application. The conclusion of this study is that the use of a lamp monitoring and control system with Internet of Things (IoT) technology is able to provide faster information to system users, and the information obtained is more accurate because it can monitor anywhere as long as the device is connected to the internet.